Anti-diabetic potential of fruit extracts of Flacourtia indica (Burm. F.) Merr-An in-vitro study (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Diabetes mellitus is one of the biggest global health problems requiring preventive and new therapeutic interventions. There is a need for safe, reliable, and cost-effective anti-diabetic drugs, and investigating medicinal plants for new anti-diabetic medications is an exciting research field. Thus, the present study examined the in-vitro anti-diabetic activity of ethanolic and aqueous extracts of Flacourtia indica (Burm. F.) Merr (Flacourtiaceae) fruits by different enzyme inhibition assay methods. Alpha-amylase and Alpha-glucosidase are the principal enzymes present in the human body which helps in the digestion of carbohydrates. Inhibition of these enzymes slows down the absorption of glucose and lowers the sugar level in the blood. Both extracts showed potent inhibitory activity against these enzymes in a dose-dependent manner. The highest percentage of inhibition is exhibited by ethanolic extract at a concentration of 100 µg/mL with an IC50 value of 84.02. The results were compared with the standard drug Acarbose, a competitive inhibitor of both enzymes. The ethanolic extract was subjected to preliminary phytochemical analysis to find out different chemical constituents. It revealed the presence of reducing sugars, flavonoids, phenolic compounds, terpenoids, fatty acids, and steroids. Therefore, the current study proved that both ethanolic and aqueous extracts of F. indica fruits possess bioactive constituents that could be responsible for the anti-diabetic activity.